Biological Efficacy of Streptomyces sp. Strain BN1 against the Cereal Head Blight Pathogen Fusarium graminearum - Jung, Boknam (Korean Society of Plant Pathology, 2013)
Fusarium head blight (FHB) caused by the filamentous fungus Fusarium graminearum is one of the most severe diseases threatening the production of small grains. Infected grains are often contaminated with mycotoxins such as zearalenone and trichothecences. During survey of contamination by FHB in rice grains, we found a bacterial isolate, designated as BN1, antagonistic to F. graminearum. The strain BN1 had branching vegetative hyphae and spores, and its aerial hyphae often had long, straight filaments bearing spores. The 16S rRNA gene of BN1 had 100% sequence identity with those found in several Streptomyces species. Phylogenetic analysis of ITS regions showed that BN1 grouped with S. sampsonii with 77% bootstrap value, suggesting that BN1 was not a known Streptomyces species. In addition, the efficacy of the BN1 strain against F. graminearum strains was tested both in vitro and in vivo. Wheat seedling length was significantly decreased by F. graminearum infection. However, this effect was mitigated when wheat seeds were treated with BN1 spore suspension prior to F. graminearum infection. BN1 also significantly decreased FHB severity when it was sprayed onto wheat heads, whereas BN1 was not effective when wheat heads were point inoculated. These results suggest that spraying of BN1 spores onto wheat heads during the wheat flowering season can be efficient for plant protection. Mechanistic studies on the antagonistic effect of BN1 against F. graminearum remain to be analyzed.